Cash plus Care: Parenting support and violence reduction programme associated with reductions in adolescent HIV-risks in South Africa: A cluster randomized trial of a DREAMS and 4Children-implemented programme 'Parenting for Lifelong Health' - Cluver, L; Meinck, F; Doubt, J; Ward, C; Lombard, C; Shenderovich, Y; Steinert, J; Romero, R; Medley, S; Redfern, A; Salah, N; De Stone, S; et al. (Wiley, 2018)
Adolescent HIV-risk behaviors are increased by family violence, low parental supervision, substance use and poverty. ‘Cash + care’ structural approaches can reduce adolescent HIV-risks, but parenting a teenager is complex and challenging. WHO, UNICEF, USAIDPEPFAR and academics developed and tested a parenting support and violence reduction program for low-resource settings, to be used as part of structural prevention programs.